(untitled) (Journal of the College of Basic Education, 2023)
This research aims to identify the effect of (active learning) and its importance in the educational processfor middle school students). The researcher followed the experimental approach because it is the appropriate approach for the nature and purpose of the research, and the researcher chose one of the experimental designs with partial control, which is the design of the non-randomized control group with a post-test only. Randomly (Al-Shaheed Ahed Mixed Middle School) to be the research sample, as the total number of students in the second intermediate grade was (120) students, divided into (4) divisions, and the sample was selected in a simple random manner, which is Division (B) to represent the experimental group of (30) ) students, and Division (C) to represent the control group of (30) students. The researcher rewarded the students of the two study groups statistically in the variables (the chronological age calculated in months, the academic achievement of fathers and mothers, the intelligence test, and the grades of the Arabic language subject for the previous academic year (2020-2021). The researcher identified five subjects of the Arabic grammar subject to be taught for the academic year (2021-2022) by the Ministry of Education for the second grade average, which he will study during the experiment period. The researcher formulated (54) behavioral goals for the subjects to be taught, prepared model teaching plans, and presented them to a group of experts and specialists to judge their validity. The necessary modifications and the behavioral goals and teaching plans in their final form are ready for application.The researcher prepared a concept acquisition test, with (21) items, of the type of objective questions (multiple choice) that measures the three levels (knowledge, understanding, and application), and its validity and difficulty coefficient were verified. The researcher applied the experiment on Monday corresponding to 11/13/2021 and ended on Monday corresponding to 1/17/2022, and the grammatical concepts acquisition test was applied on Monday corresponding to (1/17/2022). The researcher studied the two study groups (experimental and control) by himself. The researcher used the following statistical methods (t-test, square (Ca2), intelligence test, difficulty coefficient, discrimination coefficient, Vakronbach equation - and the effectiveness of false alternatives). After analyzing the results of the students’ answers and processing them statistically using the t-test for the middle samples to find out the significance of the difference at the level (0.05) between the two study groups, the following became clear: There is a statistically significant difference at the level of significance (0.05) between the average scores of the students of the experimental group who study Arabic grammar in a manner (Active learning and its importance in the educational process for second grade intermediate students) and the average scores of the students of the control group who study Arabic grammar in the traditional way in the post-test in favor of the experimental group.